State of Adenovirus 2 Deoxyribonucleic Acid in the Nucleus and Its Mode of Transcription: Studies with Isolated Viral Deoxyribonucleic Acid-Protein Complexes and Isolated Nuclei - Wallace, Robert D. (1972)
Newly replicated adenovirus 2 deoxyribonucleic acid (DNA) can be isolated from the nucleus of HeLa cells by a gentle lysis procedure as a fairly homogeneous complex with a sedimentation of 73S. The viral DNA complex can be prepared completely free from host cell DNA. The viral complex is slightly active in ribonucleic acid (RNA) synthesis in vitro. Treatment of the complex with Pronase and sodium dodecyl sulfate converts the DNA to a form which sediments at 43S. Nuclei isolated from adeno-infected cells synthesize high-molecular-weight virus-specific RNA in vitro. Optimal RNA synthesis requires a divalent cation, preferentially manganese, and relatively high salt concentrations. The synthesis of virus-specific RNA by the isolated nuclei is strongly inhibited by low doses of α-amanitine. The latter experimental result is discussed in terms of the polymerase used to transcribe the adenovirus DNA in vivo.